2004
DOI: 10.1111/j.1464-4096.2004.04821.x
|View full text |Cite
|
Sign up to set email alerts
|

The 24‐h frequency‐volume chart in adults reporting no voiding complaints: defining reference values and analysing variables

Abstract: was aimed at discerning the relationships between the FVC variables, gender and age. RESULTSThere was a linear increase in mean 24-h voiding frequency and nocturia in men, from 6.0 and 0.5 in the third decade to 8.5 and 1.6 in those aged > 70 years. Contrary to men, in women the mean 24-h frequency declined slightly in the older decades; it increased from 6.9 in the third to 8.2 in the sixth, declining to 7.8 in those aged > 70 years. Nocturia in women increased linearly, although slower than in men, from 0.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 21 publications
9
65
0
Order By: Relevance
“…The degrees of variation in urinary volumes in the CDC data set per void and per day are consistent with those previously reported for urinary volume in adults. 18 Although the CDC data demonstrate that creatinine excretion occurs at a more constant rate than urinary volume, there remains some intra-individual variation in creatinine excretion rate both between urinary voids and across days that may influence variation in biomarker concentrations when those concentrations are normalized to creatinine. Finally, other factors such as analytical imprecision can contribute to variation in measured concentrations, although relative errors in high quality analytical work should be relatively small compared with many of the other factors discussed here.…”
Section: Discussionmentioning
confidence: 99%
“…The degrees of variation in urinary volumes in the CDC data set per void and per day are consistent with those previously reported for urinary volume in adults. 18 Although the CDC data demonstrate that creatinine excretion occurs at a more constant rate than urinary volume, there remains some intra-individual variation in creatinine excretion rate both between urinary voids and across days that may influence variation in biomarker concentrations when those concentrations are normalized to creatinine. Finally, other factors such as analytical imprecision can contribute to variation in measured concentrations, although relative errors in high quality analytical work should be relatively small compared with many of the other factors discussed here.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of MEHP is 4.30 mg/l for males and 4.10 mg/l for females (CDC, 2005), so given that a mole of MEHP is 278 g/mole, the UCs are given as 1.5*10 À8 moles/l for both males and females. In a study on the frequency of urination for adults, Van Haarst et al (2004) reported on void frequencies and volumes for 1152 men and women over age 20. They found that the daily void volumes for men and women were 1.718 and 1.762 l, respectively (the specific number of men and women were not provided).…”
Section: Model Applicationfbackground Exposuresmentioning
confidence: 99%
“…Similarly, in men over 65 Blanker et al 11 report a 75th percentile of 8.3, and Latini et al 6 report a 75th percentile of 9 and a 95th percentile of 12. Even higher upper normal limits are suggested by mean F 24 s in asymptomatic men 60-69 years old reported by Homma et al 5 of 8.8 and by van Haarst et al 7 of 8.03. In Figures 3 and 4, we compare van Haarst et al's and our plots of relationships to age and V 24 .…”
Section: Subjectsmentioning
confidence: 73%
“…That reference values for F 24 must be adjusted upward as V 24 increases is not unexpected. However, a recently reported 7,8 robust tendency in asymptomatic volunteers for V avg and V max to increase as V 24 increases strongly suggests that reference Vol/Void values should also be adjusted upward as V 24 increases. Therefore, in constructing reference voiding diary values, we will use multiple regression analysis to characterize the relationships asymptomatic male population of Vol/Void and F 24 to both age and V 24 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation